Associations between maternal and offspring glucose metabolism: a 9-year follow-up of a randomised controlled trial - Nyen, Sigrid L.; Stunes, Astrid Kamilla; Evensen, Kari Anne I.; Børsting, Torunn; Syversen, Unni; Salvesen, Kjell Å.; Mørkved, Siv; Stafne, Signe N. (Frontiers in Endocrinology, 2024)
Introduction: There is increasing evidence that the in utero environment affects the health and disease risk of offspring throughout their lives. The long-term effect of maternal hyperglycaemia on offspring glucose metabolism is of interest in a public health perspective. The aim of this study was to examine the association between in utero exposure to maternal glycaemia and offspring glucose metabolism. Methods: Mother-child pairs were recruited from an RCT to prevent gestational diabetes mellitus where 855 healthy pregnant women were randomised to exercise or standard antenatal care. The original RCT detected no group differences in gestational diabetes mellitus prevalence or insulin resistance. The two groups were analysed as one group in the present study. Maternal glucose levels were assessed after 2-hour 75-gram oral glucose tolerance tests in pregnancy week ~34. Offspring outcomes were evaluated at ~9 years of age and included fasting glucose and homeostatic model assessment of insulin resistance. Multivariable regression models were performed, controlling for potential hereditary and lifestyle confounding factors. Results: Complete data were available for 105 mother-child pairs. The regression analysis showed a positive association between maternal and offspring fasting glucose that was borderline significant (beta=0.18, 95% CI [-0.00027, 0.37], p=0.050). We did not find significant associations between maternal fasting glucose and offspring insulin resistance (beta=0.080, 95% CI [-0.087, 0.25], p=0.34), or between maternal 2-hour glucose and offspring fasting glucose (beta=0.016, 95% CI [-0.038, 0.070], p=0.56) or insulin resistance (beta=0.017, 95% CI [-0.032, 0.065], p=0.49). Conclusions: Assessing a homogeneous group of healthy mother-child pairs, we found a borderline significant positive association between maternal and offspring fasting glucose, which persisted after adjustment for potential hereditary and lifestyle confounding factors. Our findings support other similar studies and highlight that improving the metabolic health of pregnant women, and women in childbearing age, should remain a key public health priority.